2005
DOI: 10.1021/ja052523i
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics of Phototropin 2 LOV2 Domain with the Linker upon Photoexcitation

Abstract: Conformational dynamics of LOV2 domain of phototropin, a plant blue light photoreceptor, is studied by the pulsed laser induced transient grating (TG) technique. The TG signal of LOV2 without the linker part to the kinase domain exhibits the thermal grating signal due to the heat releasing from the excited state and a weak population grating by the adduct formation. The diffusion coefficients of the adduct product after forming the chemical bond between the chromophore and Cys residue are found to be slightly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
189
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(213 citation statements)
references
References 33 publications
22
189
1
1
Order By: Relevance
“…However, UV-visible absorption reflects the electronic environments around the isoalloxazine ring of the FMN chromophore and cannot sense the conformational changes in the protein moiety. We therefore proposed denoting these photointermediates with a UVvisible absorption spectrum of S390 and conformational changes in the protein moiety detected by NMR (15), SAXS (16), FTIR (17,18), or transient grating (19) as S390II (37). In the present investigation, the phot proteins consisting of LOV2-linker-kinase also exhibited production of a photointermediate (S390) similar to that of LOV cores accompanied by kinase activation.…”
Section: P2l2k As a Bl-regulated Kinase With Dark Activity-p1l2kmentioning
confidence: 57%
See 1 more Smart Citation
“…However, UV-visible absorption reflects the electronic environments around the isoalloxazine ring of the FMN chromophore and cannot sense the conformational changes in the protein moiety. We therefore proposed denoting these photointermediates with a UVvisible absorption spectrum of S390 and conformational changes in the protein moiety detected by NMR (15), SAXS (16), FTIR (17,18), or transient grating (19) as S390II (37). In the present investigation, the phot proteins consisting of LOV2-linker-kinase also exhibited production of a photointermediate (S390) similar to that of LOV cores accompanied by kinase activation.…”
Section: P2l2k As a Bl-regulated Kinase With Dark Activity-p1l2kmentioning
confidence: 57%
“…Light-induced conformational changes in the linker region were detected in At phot1 with small angle x-ray scattering (SAXS) (16), FTIR spectroscopy (17,18), and transient grating (19). Recently, light-induced movement of the LOV2 domain relative to the kinase domain in At phot2 was visualized by SAXS (20).…”
mentioning
confidence: 99%
“…6,[23][24][25][26] The time profile represents the reaction kinetics as well as the thermal diffusion and molecular diffusion processes. Figure 1 shows a typical TG signal after photoexcitation of PixD in the buffer solution at a grating wavenumber q 2 = 4.0 × 10 11 m − 2 and a laser power of 0.2 mJ cm − 2 .…”
Section: Resultsmentioning
confidence: 99%
“…5). FTIR spectroscopy (26,27,36,37), CD spectroscopy (38), small angle x-ray scattering (19), and pulsed laser-induced transient gating methods (39) have shown that irradiation of LOV2-J␣ protein fragments derived from several different phototropin sources results in significant structural changes at the surface of the LOV-core. In particular, FTIR spectroscopy has indicated that light-induced formation of LOV2 390 produces progressive changes that involve regions of loops, ␣-helices, and ␤-sheets (26,27).…”
Section: Discussionmentioning
confidence: 99%